Effect of hospital interventions to improve patient flow on emergency department clinical quality indicators. Issue 12 (3rd September 2020) - Sethi, Simon; Boulind, Caroline; Reeve, Julie; Carney, Amanda; Bruijns, Stevan
Abstract : Introduction: The Royal College of Emergency Medicine highlights poor flow through hospitals as a major challenge to improving emergency department flow. We describe the effect of several hospital-wide flow interventions on Yeovil District Hospital's emergency department flow. Methods: During 2016, a design science research study addressed several areas disproportionally contributing to exit block within Yeovil District Hospital. In this follow-up study, we used a retrospective, before/after design, to describe the effect of these interventions on the ED. We used the Royal College of Emergency Medicine's clinical quality indicators (4-hour standard, time to decision-maker, 7-day unplanned reattendance, left without being seen, ambulatory patient care and patient experience). Pearson correlation coefficient (r) was used to compare variables. Wilcoxon signed-rank test was used to compare performance before and after the intervention. Results: Yeovil District Hospital emergency department was attended by 160 373 patients between August 2015 and October 2018. Mean monthly attendance was 4112 (±342) patients, mean age was 43 (±28) years with equal male/female split (49/51%). The 4-hour standard made a recovery from 92% to 97% (p=0.01) that did not correlate with a recovery in national data (r=0.09); this despite rising attendances both at Yeovil and nationally (r=0.75). All clinical quality indicators improved significantly (except unplanned reattendance and patient feedback which improved but not significantly). Discussion: The positive effect on emergency department clinical quality indicators reveals the beneficial impact of improving in-patient flow. Qualitative research is needed to better understand facilitators and barriers to flow improvement work.